Can we find positive integers m and n such that 9 + 9 2 + ⋯ + 9 m = 6 + 6 2 + ⋯ + 6 n ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Right side is 6+36(1+6+36+....)=6+9*4(1+6+36+...) is not divisible by 9
We have that 6 + 6 2 + ⋯ + 6 n 9 + 9 2 + ⋯ + 9 m = 1 ( 8 9 ( 9 m − 1 ) ) ⋅ ( 6 ( 6 n − 1 ) 5 ) = 1 On further simplification we find that 1 6 ⋅ 6 n − 1 5 ⋅ 9 m = 1 c c 1 6 ⋅ ( 3 n ) 2 n − 5 ⋅ 3 2 m + 1 = 1 As Sir @Pi Han Goh makes an observation that left hand side is divisible by 3 however, the right hand side isn't divisible by 3 . Hence, there is no solution for m and n .
Another approach 6 n = 1 6 1 + 1 5 ⋅ 9 m On the right hand side we note that 1 + 1 5 ⋅ 9 m ≡ { 0 m o d ( 1 6 ) c c c c c if m is even ± 8 m o d ( 1 6 ) c c c c if m >1 is odd
In odd case we are not going to deal since it doesn't yield any positive integer and we are left with even case. Further we note that 6 n ≡ 0 m o d ( 6 ) however, RHS of the above equation is found to be k = 1 6 1 + 1 5 ⋅ 9 m ≡ { − 4 m o d ( 6 ) if m = 2 × odd − 1 m o d ( 6 ) if m = 4 × Z + This shows that it is not possible to find positive integers m and n such that desired equations can be true .
While this is correct, your approach is very convoluted.
Notice that for 1 6 ⋅ 6 n − 1 5 ⋅ 9 m = 1 , upon division by 3, LHS is divisible by 3 but RHS is not. So there's no solution.
Log in to reply
Ahh!! I see. I have added a line to avoid unreasonable lengthy solution. You can see it. Thank you !! :)
Sir, How do I solve the following sum n = 0 ∑ ∞ [ ( n + 1 ) ( n + 2 ) 1 + 1 ! 2 + 2 ! 3 + ⋯ + n ! n + 1 ] ?
Problem Loading...
Note Loading...
Set Loading...
Note that the left-hand side is obviously divisible by 9 .
What about the right-hand side? Use the formula for the sum of a geometric series.
6 + 6 2 + ⋯ + 6 n = 6 − 1 6 ( 6 n + 1 − 1 ) = 5 6 ( 6 n + 1 − 1 )
Now, there's only a single factor of 3 as 6 n + 1 − 1 is not divisible by 3 . Thus, the right-hand side is never divisible by 9 .
Note
As user X X pointed out in the comments, there is an easier way to show that the right-hand side is not divisible by 9 :
6 + 6 2 + ⋯ + 6 n = 6 + 3 6 ( 1 + 6 2 + ⋯ + 6 n − 2 ) = 6 + 9 ⋅ 4 ( 1 + 6 2 + ⋯ + 6 n − 2 )